The Relationship between the Gospel and Culture: A Theological Analysis and Social Perspective in a Contemporary Context - Soegianto, Soegianto (Theological Journal Kerugma, 2024)
In today's era of globalization and cultural pluralism, the relationship between the Gospel and culture has become an increasingly complex issue. Various theological perspectives have developed to understand how the message of the Gospel interacts with diverse cultural values and practices. The debate surrounding accommodation or resistance to local and global cultures requires a deeper examination within the context of Christian theology. This study aims to explore the relationship between the Gospel and culture from theological and social perspectives, as well as how this relationship influences the practice of Christian faith in contemporary multicultural and dynamic societies. The approach used in this research is qualitative theological analysis, with a literature review of contextual theology texts and cultural studies. The collected data were critically analyzed to identify patterns of interaction between the Gospel and culture in the modern social context. The research finds that the Gospel can interact with culture through a dialectical process involving acceptance, adaptation, and transformation of cultural values. In some cases, culture enriches religious practices, but in other situations, there are tensions that require deep theological reflection to ensure that Gospel values are not compromised by certain cultural practices. The relationship between the Gospel and culture is dynamic and contextual. It is important for Christian theology to develop a flexible approach while adhering to the core teachings of the Gospel in the face of cultural changes. In this way, the Gospel can remain relevant and significant in the lives of contemporary societies without losing its integrity.